Pemanfaatan Limbah High Density Polyetylene (HDPE) Geomembrane Sebagai Campuran Beton Normal - Agus Hendrayana; Riza Susanti; Shifa Fauziyah (Jurnal Sipil dan Arsitektur, 2024)
High-Density Polyethylene (HDPE) is a thermoplastic polymer material processed by the heating process of petroleum. One processed product is geomembrane  sheets, commonly used to construct ponds in geothermal areas. This Final Project researched High-Density Polyethylene geomembrane  waste as an additional material mixed into ordinary or everyday concrete mixtures with fc' = 25 MPa quality. The added waste material from the geomembrane  (HDPE) is 0.5 x 0.5 cm and has been cut or chopped with a particular machine. High-density polyethylene (HDPE) content is included in the mixture in regular concrete with a volume composition of 0.00%, 0.25%, 0.50%, 0.75%, and 1.00%. The method for calculating the composition of the concrete mixture uses the American Concrete Institute (ACI) standard. The results showed that the most optimum value for obtaining the compressive strength of concrete fc' 25 MPa with the highest value of split tensile strength (3.54 MPa) was a mixture with 0.50% chopped geomembrane  (HDPE). Based on these results, waste in geothermal areas is expected to be reduced by using concrete and a mixture of chopped geomembrane  (HDPE).